2017
DOI: 10.1007/s12571-017-0655-5
|View full text |Cite
|
Sign up to set email alerts
|

Aid or abyss? Food assistance programs (FAPs), food security and livelihoods in Humla, Nepal

Abstract: Diversification of livelihoods is a commonly applied strategy for coping with economic and environmental shocks and instrumental in poverty reduction. In this paper, we have assessed the role of livelihood diversification in household well-being in Humla, a remote mountain district in west Nepal. Employing the data produced from household surveys, we developed a composite household well-being index incorporating four components and 15 indicators, and measured the effect of diversification on it. Results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 160 publications
0
23
0
Order By: Relevance
“…Qualitative research indicates that the Super Cereal was also considered inferior than the traditionally favored rice ( 49 ), although the Super Cereal was used to make foods that are acceptable and commonly consumed in this context. Different distribution and consumption amounts may have been observed if rice transfers were provided, such as the food-for-assets interventions by the World Food Programme in the west and far-west of Nepal ( 50 ). Indeed, a comparison of rice and wheat transfers from Bangladesh found that rice was preferentially given to men but wheat was channeled to women ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research indicates that the Super Cereal was also considered inferior than the traditionally favored rice ( 49 ), although the Super Cereal was used to make foods that are acceptable and commonly consumed in this context. Different distribution and consumption amounts may have been observed if rice transfers were provided, such as the food-for-assets interventions by the World Food Programme in the west and far-west of Nepal ( 50 ). Indeed, a comparison of rice and wheat transfers from Bangladesh found that rice was preferentially given to men but wheat was channeled to women ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…(3) provide poor households with employment opportunities by working on the farms or building infrastructure, for which they are paid in-kind with rice [37]. In the district of Humla, the program only benefitted the high-caste, rich landowners since they got cheap agricultural labour and road access from their lands to markets.…”
Section: Structural Flaws In Program Theorymentioning
confidence: 99%
“…The second theme emerging in our review was the concentration of power in the hands of the South Asian elite and how this impeded program reach to the poorest of the poor. In this context, the denomination of the elite is based on their status as high-caste, with its associated opportunities, privileges, and entitlements [37,[39][40][41][42]. This includes land ownership, wealth, and membership in networks that sustain their dominant social and political identities.…”
Section: Elite Capture Of Social Protection Programsmentioning
confidence: 99%
“…The area was once an epicenter of trade, and the ethnic Tibetans living there have been able to minimize food insecurity risks for centuries by using that trade to supplement their local crops with lowland foods (F€ urer-Haimendorf 1975). In 1999, this situation experienced a major change as the World Food Programme began a Food for Work initiative (see Gautam and Andersen 2017), which included a roadbuilding project to connect Humla to both China and the rest of Nepal; local villagers were offered white rice as an incentive to work on this road.…”
Section: Infrastructure Change and Food Security In Upper Humla District Nepalmentioning
confidence: 99%